Establishment of a Refined Oral Glucose Tolerance Test in Pigs, and Assessment of Insulin, Glucagon and Glucagon-Like Peptide-1 Responses. - Elin Manell; Patricia Hedenqvist; Anna Svensson; Marianne Jensen-Waern (PLoS ONE, 2016)
Diabetes mellitus is increasing worldwide and reliable animal models are important for progression of the research field. The pig is a commonly used large animal model in diabetes research and the present study aimed to refine a model for oral glucose tolerance test (OGTT) in young growing pigs, as well as describing intravenous glucose tolerance test (IVGTT) in the same age group. The refined porcine OGTT will reflect that used in children and adolescents. Eighteen pigs were obtained one week after weaning and trained for two weeks to bottle-feed glucose solution, mimicking the human OGTT. The pigs subsequently underwent OGTT (1.75 g/kg BW) and IVGTT (0.5 g/kg BW). Blood samples were collected from indwelling vein catheters for measurements of glucose and the diabetes related hormones insulin, glucagon and active glucagon-like peptide-1. The study confirmed that pigs can be trained to bottle-feed glucose dissolved in water and thereby undergo an OGTT more similar to the human standard OGTT than previously described methods in pigs. With the refined method for OGTT, oral intake only consists of glucose and water, which is an advantage over previously described methods in pigs where glucose is given together with feed which will affect glucose absorption. Patterns of hormonal secretion in response to oral and intravenous glucose were similar to those in humans; however, the pigs were more glucose tolerant with lower insulin levels than humans. In translational medicine, this refined OGTT and IVGTT methods provide important tools in diabetes research when pigs are used as models for children and adolescents in diabetes research.